Safety Assessment on Serious Adverse Events of Targeted Therapeutic Agents Prescribed for RAS Wild-Type Metastatic Colorectal Cancer: Systematic Review and Network Meta-Analysis - Choi, Yeo Jin; Choi, Chang Young; Rhie, Sandy Jeong; Shin, Sooyoung (International Journal of Environmental Research and Public Health, 2022)
Despite substantially elevated risk of serious adverse events (SAEs) from targeted therapy in combination with chemotherapy, comprehensive pharmacovigilance research is limited. This study aims to systematically assess SAE risks of commonly prescribed targeted agents (bevacizumab, cetuximab, and panitumumab) in patients with rat sarcoma viral oncogene homolog (RAS) wild-type metastatic colon cancer. Keyword searches of Cochrane Library, Clinical Key and MEDLINE were conducted per PRISMA-NMA guidelines. Frequentist network meta-analysis was performed with eight randomized controlled trials to compare relative risk (RR) of 21 SAE profiles. The risks of hematological, gastrointestinal, neurological SAE were insignificant among targeted agents (p > 0.05). The risk of serious hypertension was substantially elevated in bevacizumab-based chemotherapy (p < 0.05), whereas panitumumab-based chemotherapy had markedly elevated risk of serious thromboembolism (RR 3.65; 95% CI 1.30–10.26). Although both cetuximab and panitumumab demonstrated increased risk of serious dermatological and renal toxicities, panitumumab-based chemotherapy has relatively higher risk of skin toxicity (RR 15.22; 95% CI 7.17–32.35), mucositis (RR 3.18; 95% CI 1.52–6.65), hypomagnesemia (RR 20.10; 95% CI 5.92–68.21), and dehydration (RR 2.81; 95% CI 1.03–7.67) than cetuximab-based chemotherapy. Thus, further studies on risk stratification and SAE management are warranted for safe administration of targeted agents.
Keywords: Antibodies, Monoclonal; Antineoplastic Agents; Antineoplastic Combined Chemotherapy Protocols; Bevacizumab; Cetuximab; Colonic Neoplasms; Colorectal Neoplasms; Humans; Network Meta-Analysis; Panitumumab; Rectal Neoplasms; adverse events; bevacizumab; cetuximab; colorectal cancer; metastatic cancer; panitumumab; pharmacovigilance